Save the day! - King, Trey.; Kiernan, Kenny; LEGO Media (Firm); WB Television Network (New York : Scholastic Inc., 2013)
"The Joker, Bane, Poison Ivy, and Harley Quinn are robbing banks and plotting a terrible crime against Gotham City. Superman, Robin, and Catwoman are here to help. But even with his friends, will Batman be able to stop the crooked criminals in time?"--P. [4] of cover.
Keywords: Batman, -- (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Superman (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Superheroes -- Comic books, strips, etc. -- Juvenile fiction; LEGO toys -- Comic books, strips, etc. -- Juvenile fiction; Superheroes -- Fiction; LEGO toys -- Fiction; Graphic novels; Adventure comic books, strips, etc; Graphic novels